Estudo energético da produção de biocombustível a partir do milho - Salla, Diones Assis; Badiz Furlaneto, Fernanda de Paiva; Cabello, Cláudio [UNESP]; Kanthack, Ricardo Augusto Dias (Universidade Federal de Santa Maria (UFSM), 2010)
This research analyzed the energetic consumption of etanol from the corn crops (Zea mays 14 The field surveys were carried out in the Midle Paranapanema River Region, São Paulo state, Brazil, in the period from January to December 2007 The energy consumption on stage of production and industrial processing of grain were evaluated It was verified that the total energetic cost of the crop production corresponded to 15,633 7MJ ha(-1), and the most onerous item was the inputs (77 5%) In the industrial step, the energetic consumption was equivalent to 3.882.2MJ r(-1) The operations of hydrolysis, saccharification and treatment of the broth represented 50 2% of the total energetic expenditure It was also observed an energetic cost of 7 9MJ L(-1) in relation to the atonal produced in the main crop production operations, and II 8MJ L(-1) in the industrial processing The energy balance of crop production and industrialization was of 1 2MJ.
Energetic study of ethanol production from the corn crops
Keywords: Zea mays L.; energy balance; renewable energy; environmental sustainability